2015
DOI: 10.1016/j.jmoldx.2014.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of HaloPlex Amplification for Sequence Capture and Massively Parallel Sequencing of Arrhythmogenic Right Ventricular Cardiomyopathy–Associated Genes

Abstract: The genetic basis of arrhythmogenic right ventricular cardiomyopathy (ARVC) is complex. Mutations in genes encoding components of the cardiac desmosomes have been implicated as being causally related to ARVC. Next-generation sequencing allows parallel sequencing and duplication/deletion analysis of many genes simultaneously, which is appropriate for screening of mutations in disorders with heterogeneous genetic backgrounds. We designed and validated a next-generation sequencing test panel for ARVC using HaloPl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Green et al ., 19 have recently showed that patients’ DNA samples were successfully sequenced after HaloPlex capture, with >99% of targeted nucleotides in the panel covered by >20×. 19 Similar results were obtained by Berglund et al ., 16 demonstrating that virtually all SNVs in their study (>99%) were covered by at least one sequence read and >96% of the variants were covered at a sequence depth of at least 30×. However, both of these studies have been using HMW DNA and targeted HaloPlex panels.…”
Section: Discussionsupporting
confidence: 68%
“…Green et al ., 19 have recently showed that patients’ DNA samples were successfully sequenced after HaloPlex capture, with >99% of targeted nucleotides in the panel covered by >20×. 19 Similar results were obtained by Berglund et al ., 16 demonstrating that virtually all SNVs in their study (>99%) were covered by at least one sequence read and >96% of the variants were covered at a sequence depth of at least 30×. However, both of these studies have been using HMW DNA and targeted HaloPlex panels.…”
Section: Discussionsupporting
confidence: 68%
“…Targeted sequencing of gene panels is an alternative to WES and has been widely used in research and is increasingly applied in clinical settings [ 13 ]. In the ICC setting, small gene panels have been used for specific ICCs, including long QT syndrome (LQTS), hypertrophic cardiomyopathy (HCM), dilated cardiomyopathy (DCM) and arrhythmogenic right ventricular cardiomyopathy (ARVC) [ 14 16 ]. Multiple workflows and bioinformatics pipelines are needed to run these various ICC gene panels, and gene coverage is such that Sanger sequencing ‘fill in’ is needed, which has very major manpower implications.…”
Section: Introductionmentioning
confidence: 99%
“…So far, 84 site mutations of DSC2 and 148 site mutations of DSP have been reported in ARVC. 16) DSP p. R1207K was the first reported and was detected in the present case of exercise-induced malignant arrhythmia in a teenager. At the same time, we confirmed that the heterozygous missense variants carried by this patient were inherited from his father.…”
Section: Discussionmentioning
confidence: 56%